SYNTHESIS DIBENZIL IS REGISTERED THROUGH THE POLYMERIZED POLYMERYLENE AS ALTERNATIVE RECYCLE PLASTIC RECYCLE - Suwardi Suwardi; Crys Fajar Partana; Agus Salim (Institute of Research and Community Services, Universitas Negeri Yogyakarta, 2005)
Synthesis dibenzyl terephathalate were done through PET softdrinkbottles degradation by refluxing in benzyl alcohol at 14 C temperature for 20, 24. and 28 hours in the presence of zinc acetate catalyst. The result of degradation was purified by recristalization in methanol and then melting point (mp), FTIR, I H NMR spectra, and TLC spot were determined. The melting point of product degradation.for 28 hours was 98-99